Restrictive eating: Associated with suicide attempts, but not acquired capability in residential patients with eating disorders. (30th January 2016) - Witte, Tracy K.; Zuromski, Kelly L.; Gauthier, Jami M.; Smith, April R.; Bartlett, Mary; Siegfried, Nicole; Bodell, Lindsay; Goodwin, Natalie
Highlights: Investigation of patients in a residential eating disorder facility (N = 100). Recent fasting associated with lifetime suicide attempts. Recent vomiting and laxative use associated with acquired capability for suicide.